Effects of Altitude Differences on the Performance of Broiler Chicken Kept in Closed House Cage - Z. R. Nugraini; L. D. Mahfudz; S. Kismiati (Jurnal Sain Peternakan Indonesia, 2022)
This study aimed to examine the effect of differences in altitude on the performance of broiler chickens. The experimental design used was a completely randomized design (CRD) with 3 treatments and 8 replications. For this research, the broiler chickens were reared in closed house cages at different altitudes: lowlands, medium lands, and highlands with the same Standard Operation Procedure (SOP). The treatments applied were T1 (broilers reared at an altitude of ± < 600 meters), T2 (broilers reared at an altitude of ± 800 – 1000 meters) and T3 (broilers reared at an altitude of ± > 1000 meters). The data were analyzed to determine the treatment effect using Duncan's Multiple Distance Test. The parameters measured were feed consumption, body weight gain (WG), feed conversion ratio (FCR), index performance (IP) and income over feed cost (IOFC). The results showed that altitude had a significant effect (P<0.05) on body weight gain (WG) in the finisher phase, feed conversion ratio (FCR) in the starter phase and finisher phase, index performance (IP) in the starter phase and finisher phase as well as income over feed cost (IOFC). From this study, it can be concluded that the performance of broiler chickens in the medium-altitude is better than the lowlands and highlands, and economically it is more profitable than rearing them in the highlands.